A rare case of pseudoglandular schwannoma - Gökalp Satıcı, Fadime Eda; Sayar, Hamide (Journal of Surgery and Medicine, 2022)
A pseudoglandular schwannoma is a rare benign tumor. Controversy in the literature regarding the histogenesis of pseudoglandular schwannoma exists. Histological features of pseudoglandular schwannomas are different than those found in classical schwannomas. A patient with pseudoglandular schwannomas has a good prognosis, and no cases of recurrence have been reported in the literature.